Primary Cilia: A Cellular Regulator of Articular Cartilage Degeneration - Haiqi Zhou; Sha Wu; Huixian Ling; Changjie Zhang; Ying Kong (Stem Cells International)
Osteoarthritis (OA) is the most common joint disease that can cause pain and disability in adults. The main pathological characteristic of OA is cartilage degeneration, which is caused by chondrocyte apoptosis, cartilage matrix degradation, and inflammatory factor destruction. The current treatment for patients with OA focuses on delaying its progression, such as oral anti-inflammatory analgesics or injection of sodium gluconate into the joint cavity. Primary cilia are an important structure involved in cellular signal transduction. Thus, they are very sensitive to mechanical and physicochemical stimuli. It is reported that the primary cilia may play an important role in the development of OA. Here, we review the correlation between the morphology (location, length, incidence, and orientation) of chondrocyte primary cilia and OA and summarize the relevant signaling pathways in chondrocytes that could regulate the OA process through primary cilia, including Hedgehog, Wnt, and inflammation-related signaling pathways. These data provide new ideas for OA treatment.